Reviewing the Applications of Internet of Things in Construction Projects - Alzubi, K.M. (Institute of Electrical and Electronics Engineers Inc., 2022)
The Internet of Things (IoT) is pervasive across nearly all industries, and construction is no exception. The use of IoT in construction enhances the management, development, and monitoring of infrastructure and structures. It also reduces the drawbacks of traditional approaches, such as their proneness to errors, time and expense constraints, and risks. The study's goal is to look at different areas where IoT can be used in the building industry. The study examines numerous elements of IoT adoption in the construction industry, including safety, decision-making, monitoring, productivity, and performance applications, as well as the constraints of the technologies utilized. This aids in determining the areas in which the Internet of Things can be used to improve the building business. The use of IoT enhances the efficiency with which construction projects are completed, as well as how the use of new technologies for monitoring will result in more effective monitoring. As a result, data regarding the building site may be collected efficiently, correctly, and in real time, allowing management to make better decisions. Â© 2022 IEEE.